Investigating the effects of D-alanine on pituitary intracellular signalling: a comparison with D-serine - Naidoo, K (2016)
The D-amino acid, D-alanine, is a co-agonist of the N-methyl-D-Aspartate receptor (NMDAR), and an agonist of the glycine receptor (GlyR). In the rat, D-alanine is highly concentrated in the pituitary gland, where it is localized to adrenocorticotropic hormone (ACTH) containing cells. This suggests that D-alanine may influence the release of ACTH, and ultimately the secretion of the stress hormone, corticosterone. Previous studies have shown that ACTH secretion from pituitary cells involves CREB and ERK1/2 signalling. We have, therefore, investigated the influence of D-alanine on the levels of these signalling proteins (western blot) and ACTH (ELISA) in cultures of the AtT-20 mouse pituitary tumour cell-line. For comparison, the effect of D-serine, a co-agonist of central NMDARs, but not GlyRs, was also examined.